Periprosthetic joint infection following hip hemiarthroplasty: factors associated with infection and treatment outcome. (1st December 2022) - Bourget-Murray, Jonathan; Horton, Isabel; Morris, Jared; Bureau, Antoine; Garceau, Simon; Abdelbary, Hesham; Grammatopoulos, George
Abstract : Aims: The aims of this study were to determine the incidence and factors for developing periprosthetic joint infection (PJI) following hemiarthroplasty (HA) for hip fracture, and to evaluate treatment outcome and identify factors associated with treatment outcome. Methods: A retrospective review was performed of consecutive patients treated for HA PJI at a tertiary referral centre with a mean 4.5 years' follow-up (1.6 weeks to 12.9 years). Surgeries performed included debridement, antibiotics, and implant retention (DAIR) and single-stage revision. The effect of different factors on developing infection and treatment outcome was determined. Results: A total of 1, 984 HAs were performed during the study period, and 44 sustained a PJI (2.2%). Multiple logistic regression analysis revealed that a higher CCI score (odds ratio (OR) 1.56 (95% confidence interval (CI) 1.117 to 2.187); p = 0.003), peripheral vascular disease (OR 11.34 (95% CI 1.897 to 67.810); p = 0.008), cerebrovascular disease (OR 65.32 (95% CI 22.783 to 187.278); p < 0.001), diabetes (OR 4.82 (95% CI 1.903 to 12.218); p < 0.001), moderate-to-severe renal disease (OR 5.84 (95% CI 1.116 to 30.589); p = 0.037), cancer without metastasis (OR 6.42 (95% CI 1.643 to 25.006); p = 0.007), and metastatic solid tumour (OR 15.64 (95% CI 1.499 to 163.087); p = 0.022) were associated with increasing PJI risk. Upon final follow-up, 17 patients (38.6%) failed initial treatment and required further surgery for HA PJI. One-year mortality was 22.7%. Factors associated with treatment outcome included lower preoperative Hgb level (97.9 g/l (SD 11.4) vs 107.0 g/l (SD 16.1); p = 0.009), elevated CRP level (99.1 mg/l (SD 63.4) vs 56.6 mg/l (SD 47.1); p = 0.030), and type of surgery. There was lower chance of success with DAIR (42.3%) compared to revision HA (66.7%) or revision with conversion to total hip arthroplasty (100%). Early-onset PJI (≤ six weeks) was associated with a higher likelihood of treatment failure (OR 3.5 (95% CI 1.2 to 10.6); p = 0.007) along with patients treated by a non-arthroplasty surgeon (OR 2.5 (95% CI 1.2 to 5.3); p = 0.014). Conclusion: HA PJI initially treated with DAIR is associated with poor chances of success and its value is limited. We strongly recommend consideration of a single-stage revision arthroplasty with cemented components. Cite this article: Bone Jt Open  2022;3(12):924–932.